Prevention of the Evolution of Workers' Hearing Loss from Noise-Induced Hearing Loss in Noisy Environments through a Hearing Conservation Program - Fonseca,Vinicius Ribas (2016)
Introduction Noise-induced hearing loss (NIHL) is a serious problem for workers and therefore for businesses. The hearing conservation program (HCP) is a set of coordinated measures to prevent the development or evolution of occupational hearing loss, which involves a continuous and dynamic process of implementation of hearing conservation routines through anticipation, recognition, evaluation, and subsequent control of the occurrence of existing environmental risks or of those thatmay exist in the workplace and lead to workers hearing damage. Objective The aim of this study was to evaluate the effectiveness of the HCP in preventing further hearing loss in workers with audiograms suggestive of NIHL. The audiometric tests and medical records of 28 furniture company workers exposed to noise were reviewed and monitored for 2 years. Methods This retrospective, cross-sectional study examined five audiometric tests in the medical records (on admission and every semester) of 28 workers in a furniture company (totaling 140 audiometric exams) following the introduction of the HCP. Results Data analysis showed no differences between the audiometric tests conducted on admission and those performed every semester. Conclusions The HCP implemented was effective in preventing the worsening of hearing loss in workers already with NIHL when exposed to occupational noise. Therefore, such a measure could be useful for the employment of workers with hearing loss in job sectors that have noise exposure.